2018
DOI: 10.1016/j.jgr.2017.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Korean Red Ginseng extracts on drug-drug interactions

Abstract: BackgroundGinseng has been the subject of many experimental and clinical studies to uncover the diverse biological activities of its constituent compounds. It is a traditional medicine that has been used for its immunostimulatory, antithrombotic, antioxidative, anti-inflammatory, and anticancer effects. Ginseng may interact with concomitant medications and alter metabolism and/or drug transport, which may alter the known efficacy and safety of a drug; thus, the role of ginseng may be controversial when taken w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…Ginsenosides Rg1, Re, and Rh1 and R1 saponins show better bioavailability than ginsenosides Ra3, Rb1, Rd, Rg3, and Rh2 saponins. In humans, the half-lives (T1/2) of saponins are usually less than 24 hours [ [24] , [25] , [26] ]. Possible drug interactions have been reported between P. ginseng and warfarin, phenelzine, and alcohol.…”
Section: Main Bodymentioning
confidence: 99%
“…Ginsenosides Rg1, Re, and Rh1 and R1 saponins show better bioavailability than ginsenosides Ra3, Rb1, Rd, Rg3, and Rh2 saponins. In humans, the half-lives (T1/2) of saponins are usually less than 24 hours [ [24] , [25] , [26] ]. Possible drug interactions have been reported between P. ginseng and warfarin, phenelzine, and alcohol.…”
Section: Main Bodymentioning
confidence: 99%
“…Red ginseng (RG) (Panax ginseng; harvested after at least 6 years) has anti-inflammatory effects and fewer side effects than fresh or white ginseng [4]. Korean red ginseng (KRG) is an effective natural drug that possesses various biological activities, including boosting the immune system[1,5,6]. Ginsenosides are the main ingredients of KRG and their value in neurodegenerative disease has been studied extensively [7].…”
Section: Introductionmentioning
confidence: 99%
“…CAA has been found to induce hepatotoxicity, neurotoxicity and nephrotoxicity (McDonald et al, 2003;Rzeski et al, 2004). Some reports about the pharmacokinetic interactions between ginsenosides and cytochrome CYP enzymes revealed that different ginsenosides can affect CYP enzyme activities (Kawase et al, 2009;Kim et al, 2018;Liu et al, 2006). Changes in these activities might affect CP metabolism.…”
Section: Introductionmentioning
confidence: 99%